2014
DOI: 10.1016/j.aju.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of antisperm antibodies, intratesticular haemodynamics and the surgical approach to varicocelectomy on seminal variables

Abstract: ObjectiveTo evaluate the effect of antisperm antibodies (ASAs), hormonal levels, intratesticular haemodynamics and the surgical approach on the outcomes of varicocelectomy in infertile men, as assessed by seminal variables.Patients and methodsIn a prospective case-series study, 82 infertile men with varicocele (35 left and 47 bilateral) were evaluated. The preoperative assessment included a physical examination, semen analysis, assessment of ASAs in seminal plasma, hormonal levels (follicle-stimulating hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…A factor that could explain this may be the assumption that in the presence of high oxidative stress and denatured DNA spermatogenesis may be impaired. Other factors that may be essential for spermatogenesis and that were previously found to be significant predictors of success after repair are a good preoperative testicular blood supply and normal Sertoli cell and Leydig cell secretory function [17] . Whilst in another study, preoperative serum FSH and testosterone concentrations were predictors of improvement after varicocelectomy [53] .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A factor that could explain this may be the assumption that in the presence of high oxidative stress and denatured DNA spermatogenesis may be impaired. Other factors that may be essential for spermatogenesis and that were previously found to be significant predictors of success after repair are a good preoperative testicular blood supply and normal Sertoli cell and Leydig cell secretory function [17] . Whilst in another study, preoperative serum FSH and testosterone concentrations were predictors of improvement after varicocelectomy [53] .…”
Section: Discussionmentioning
confidence: 97%
“…Our present results are in agreement with many studies regarding the laterality of varicocelectomy and the response in different grades of varicocele. Many studies have reported a statistically non-significant difference between bilateral and unilateral repair with similar seminograms [16] , [17] , [50] . In addition, some authors found no clear correlation between ligated vein size (individual or cumulative) and improvements in seminal variables [51] ; whilst others have found a significant difference in favour of bilateral repair [49% (54/110) vs 36% (53/146), P < 0.05] [52] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Ross et al [37] have observed that neither varicocele nor varicocelectomy alter testicular blood flow in men, whereas experimental data demonstrated that varicocele increased testicular blood flow, which might be the reason for testicular hyperthermia [38,39]. Used as markers, Ener et al [40] reported that both EDV and PSV were increased significantly after varicocelectomy, indicating a restoration of testicular microcirculation, whereas, in another study, elevation of EDV after varicocelectomy in the affected side was associated with a successful outcome [41]. In our present study, decreased EDV values of patients in Group B may correspond to clinically meaningful impedance of blood flow inside the testicular parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Thus, the clinical utility of ASA testing remains questionable as the presence of ASA neither predict semen quality improvement after varicocele repair nor direct a different form of treatment. 20 …”
Section: Specialized Sperm Functional Tests In Varicocele-associated mentioning
confidence: 99%